Determination of multipath error by using GPS dual frequency data / Ahmad Azizul Azwan Yaacob - Azwan Yaacob, Ahmad Azizul (2013)
The purpose of this project is to determine multipath error by using GPS dual frequency data, LI and L2. The RTNEX (Receiver Independent Exchange) data from six MASS (Malaysia Active GPS System) stations are acquired from DSMM (Department of Survey and Mapping Malaysia) for analysis purposes. The stations are BEHR, BINT, KUAN, LABU, USMP and UTMJ. The analysis for this project divided by three categories, namely analysis on surrounding area of MASS station, analysis on satellite track and analysis on rainfall effect. For analysis on surrounding area, all RTNEX data from six stations were used, while for analysis on satellite track, RTNEX data from BINT station and LABU station were used, and for analysis on rainfall, RTNEX data from KUAN station and UTMJ station were used based on data of rainfall from MMD (Malaysian Meteorological Department). TEQC (Translating, Editing, Quality Check) software were used to extract the RTNEX data and generate several file such as MP1 (multipath carrier LI), MP2 (multipath carrier L2) and report file for analysis purpose. MATLAB software were used for plotting graph to perceive the value of multipath for each analysis. The result from analysis on surrounding area obtained, shows the residential area and urban area has highest value of multipath error and open area has lowest value of multipath error, while the result from analysis on satellite track obtained, and shows satellite track farthest from MASS station has highest value of multipath error, and satellite track nearest to MASS station has lowest value of multipath error. The result from analysis on rainfall shows the value of multipath error not influenced by reading of rainfall. Based on the result from all analysis in this project, that will contribute in enhancing the efficiency of data transmission process.